Association of Immediate Postpartum Etonogestrel Implant Insertion and Venous Thromboembolism [01J]. (May 2020) - Floyd, Jessica L.; Beasley, Anitra; Swaim, Laurie S.; Turrentine, Mark; Nijjar, J. Biba
Abstract : INTRODUCTION: Placement of the etonogestrel contraceptive implant (ECI) during the delivery admission provides immediate, reliable and convenient contraception. The implant manufacturer recommends delaying placement until 21 days postpartum due to concern for increased risk of postpartum venous thromboembolism (VTE). This study compares the rate of VTE between women with and without delivery admission contraceptive implant insertion. METHODS: The Nationwide Readmissions Database from 2016 was used to identify women with a singleton delivery, immediate postpartum ECI, and readmission for VTE within 30 days of discharge. Those with a prior history of VTE or anticoagulant therapy were excluded. These women were compared to the number of women readmitted for VTE who did not have the contraceptive implant placed during delivery admission. RESULTS: Of 3, 387, 120 deliveries, 8, 369 women underwent ECI placement during the delivery admission. Of women readmitted with VTE, 7 had received a postpartum ECI (0.8 per 1, 000 deliveries) compared to 1, 192 without an ECI (0.4 per 1, 000 deliveries), Odds Ratio (OR) 2.41; 95th CI 0.58-9.89. The rates of diabetes, thrombophilia, lupus and cesarean delivery did not differ between groups. Women that underwent ECI placement were younger, on Medicaid, smoked, had hypertension, intrauterine growth restriction, peripartum infection, or postpartum hemorrhage (P<.01). Adjusting for these confounders showed no impact, adjusted OR 1.80; 95th CI 0.44-7.37. CONCLUSION: No significant difference was noted in the rate of VTE in women after immediate postpartum insertion of the ECI, suggesting that the implant may not be associated with VTE if placed in the immediate postpartum period.